PENGARUH FAKTOR-FAKTOR INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA PT. PEGADAIAN PERSERO SURAKARTA - Arista, Lilik Lia (Journal of Innovation in Business and Economics, 2015)
This study aims to determine the factors that influence the tendency of accounting fraud and determine what factors most influence on the tendency of the accounting fraud at PT. Pegadaian. The research instrument in this study was a questionnaire on the scatterplot directly to managers, managers and financial staff Pegadaian Area Surakarta. The data analysis technique used is the test data quality, classic assumption test and multiple linear regression analysis. Results of the dependent variable in this case the tendency of accounting fraud amounting to 31.7% by independent variable. This can be seen from the value of Adjusted R Square of 0.317. While 68.3% of dependent variable influenced by other variables outside the model study.Keywords: Accounting Fraud Trends, Pawnshop, Surakarta